1974
DOI: 10.1073/pnas.71.8.3260
|View full text |Cite
|
Sign up to set email alerts
|

Ansamycin Biogenesis: Studies on a Novel Rifamycin Isolated from a Mutant Strain of Nocardia mediterranei

Abstract: A novel ansamycin, rifamycin W, was isolated from a mutant strain of Nocardia mediterranei. The metabolic origin of rifamycin W was studied by 13C nuclear magnetic resonance spectroscopy. Examination of the proton-decoupled pulse and Fourier transform 13C spectra of rifamycin W biogenetically enriched with [1-13C1-, [1-'3C~acetate has revealed that In a previous publication (9) describing the biosynthesis of rifamycin S, we proposed a general scheme for the biogenesis of the ansamycin carbon skeleton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…The single and double crossover mutants were screened by Southern hybridization, cultured in YMG liquid medium for 7 days and the secondary metabolites analysed by HPLC and ESI-MS. The results indicated that inactivation of rif-orf4 and riforf13 did not have any effect on the production of rifamycin B, while mutants of rif-orf16 produced a mixture of rifamycin SV and rifamycin B. Inactivation of rif-orf5, however, inhibited rifamycin B production and caused the accumulation of rifamycin W, an analogue previously isolated from a mutant strain of A. mediterranei strain AE/1 obtained by mutagenesis of spores with nitroguanidine (White et al, 1974). Rifamycin W production was confirmed by mass spectrometry and 1 H-NMR analysis.…”
Section: Inactivation Of the P450-dependent Monooxygenases (Rif-orfs mentioning
confidence: 75%
See 2 more Smart Citations
“…The single and double crossover mutants were screened by Southern hybridization, cultured in YMG liquid medium for 7 days and the secondary metabolites analysed by HPLC and ESI-MS. The results indicated that inactivation of rif-orf4 and riforf13 did not have any effect on the production of rifamycin B, while mutants of rif-orf16 produced a mixture of rifamycin SV and rifamycin B. Inactivation of rif-orf5, however, inhibited rifamycin B production and caused the accumulation of rifamycin W, an analogue previously isolated from a mutant strain of A. mediterranei strain AE/1 obtained by mutagenesis of spores with nitroguanidine (White et al, 1974). Rifamycin W production was confirmed by mass spectrometry and 1 H-NMR analysis.…”
Section: Inactivation Of the P450-dependent Monooxygenases (Rif-orfs mentioning
confidence: 75%
“…White and co-workers experimentally showed that washed mycelium from a rifamycin B-producing strain of A. mediterranei transformed rifamycin W into rifamycin B (White et al, 1974). As inactivation of rif-orf5 resulted in mutants that produce rifamycin W, we propose that Rif-Orf5 functions in the oxidative cleavage of the C12-C29 double bond of rifamycin W, leading to a rearrangement reaction to form a ketal structure (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1975, a mutant strain designated ATCC 21789 that is able to produce a sole product of rifamycin B without the addition of barbiturate was isolated (11), and a related strain, S699 (5), has been widely used in laboratory research ever since (1,2,4,6).…”
mentioning
confidence: 99%
“…solated in 1957 at St. Raphael, France (8), Amycolatopsis mediterranei original strain ATCC 13685 synthesizes a collection of rifamycin complexes, while a single fermentation product of rifamycin B, whose derivatives are effectively used to treat mycobacterial infections (11), could be obtained only if sodium diethyl barbiturate was added to the medium (9). In 1975, a mutant strain designated ATCC 21789 that is able to produce a sole product of rifamycin B without the addition of barbiturate was isolated (11), and a related strain, S699 (5), has been widely used in laboratory research ever since (1,2,4,6).…”
mentioning
confidence: 99%